The ageing of the world’s population: a new challenge - Kalache, Alexandre; Veras, Renato P.; Ramos, Luiz Roberto (Revista de Saúde Pública, 1987)
Ageing has now become a universal phenomenon, of increasing importance to developed and developing countries alike. In this, the first of a series of articles on ageing in developing countries, the actual demographic revolution is discussed, with special reference to Brazil. Estimates are provided up to the year 2025. The article analyses the factors which are responsible for this ageing process - such as the rapid decline in fertility and mortality rates that many Third Word countries have been experiencing over the last few years - and the various gradual stages of this process, which is usually referred to as the 'epidemiological transition', are discussed. The consequences for any society with a population that is gradually becoming older are considerable, and are of particular importance for the Health Sector. The article discusses the changing morbidity and mortality patterns and the concept of autonomy as a possible way to quantify quality of life is introduced. On this particular point a suggestion is made to redefine the concept of 'Ageing', in order to take into consideration the context in which senior adults in the Third World live. Finally, the article addresses itself to points relating to the interaction of ageing and social change. That there is such an interaction is apparent in developing countries and this raises questions to which answers could be found through the use of the epidemiological method.